The Effects of Review Presentation Formats on Consumers' Purchase Intention - Du, Rong; Li, Cong; Liu, Yuming (Journal of global information management, 2021)
Perception of products has becoming one of the most important factors influencing consumers’ purchase intention in the context of online shopping. Thus, enriching and studying review presentation formats have been significant things for practitioners and researchers. This study employed dual coding theory and telepresence theory to investigate the effects of review presentation formats (text-based reviews, image-based reviews and video-based reviews) on consumers’ purchase intention, and then analysed the moderation effect of product type. The 3×2 between-subject situational experiment and 3×2 within-subject eye-tracking experiment design were separately applied to test the hypotheses. The results manifested that review presentation formats exactly could generate different impacts on consumers’ purchase intentions. And product type moderated the impact of presentation formats on purchase intentions. Hence, this research considered online vendors should pay more attention to image-based and video-based reviews, moreover take the product type into account.